2009
DOI: 10.1111/j.1750-3841.2009.01233.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality Changes of Prerigor Filleted Atlantic Salmon (Salmo salar L.) Packaged in Modified Atmosphere Using CO2 Emitter, Traditional MAP, and Vacuum

Abstract: Pieces of prerigor salmon fillets were packaged in modified atmosphere (60% CO(2) and 40% N(2)) and in vacuum. The MA packages had a gas to product volume ratio (g/p ratio) of 3/1 (traditional MAP) and 1/1 (packaged with a CO(2) emitter). All the samples were stored at 1.2 degrees C for 25 d. The MA packages had lower bacterial growth during storage compared to vacuum packages. The analyses of 16S rRNA at day 22 indicated a similar bacterial diversity, independent of packaging methods, dominated by Photobacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
65
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 54 publications
7
65
1
1
Order By: Relevance
“…The shelf life of vacuum packaged CSS kept under refrigerated conditions ( 4 C) is generally 3e5 weeks, as indicated by the producers (Leroi, Arbey, Joffraud, & Chevalier, 1996Rørvik et al, 1991). However, modified atmosphere packaging (MAP) has shown to improve shelf life compared to vacuum packaging in some studies (Cakli, Kilinc, Dincer, & Tolasa, 2006;Hansen et al, 2009;Paludan-Muller, Dalgaard, Huss, & Gram, 1998;Szabo & Cahill, 1999). A gas mixture of 70% CO 2 , 25% N 2, and 5% O 2 gave promising results for sliced CSS with respect to microbial, chemical, and sensory evaluation compared to mixtures with either more or less CO 2 (Civera, Amerio, & Parisi, 1993).…”
Section: Packaging and Storagementioning
confidence: 98%
“…The shelf life of vacuum packaged CSS kept under refrigerated conditions ( 4 C) is generally 3e5 weeks, as indicated by the producers (Leroi, Arbey, Joffraud, & Chevalier, 1996Rørvik et al, 1991). However, modified atmosphere packaging (MAP) has shown to improve shelf life compared to vacuum packaging in some studies (Cakli, Kilinc, Dincer, & Tolasa, 2006;Hansen et al, 2009;Paludan-Muller, Dalgaard, Huss, & Gram, 1998;Szabo & Cahill, 1999). A gas mixture of 70% CO 2 , 25% N 2, and 5% O 2 gave promising results for sliced CSS with respect to microbial, chemical, and sensory evaluation compared to mixtures with either more or less CO 2 (Civera, Amerio, & Parisi, 1993).…”
Section: Packaging and Storagementioning
confidence: 98%
“…On the other hand, an increased g/p ratio in a package of modified atmosphere can be compensated by use of a CO 2 emitter, which develops CO 2 gas after sealing the package. Studies performed on fillets from farmed Atlantic cod and Atlantic salmon have shown that a CO 2 emitter can compensate for a g/p ratio of 4/1 and 3/1, respectively (Hansen, Mørkøre, Rudi, Olsen & Eie, 2007;Hansen, Mørkøre, Rudi, Rødbotten et al, 2009). The CO 2 emitter additionally functions as a liquid absorbent pad, and it enables low g/p ratios without packaging collapse.…”
Section: Introductionmentioning
confidence: 98%
“…Odor of raw fish products, which can be characterized by use of different attributes related to fresh fish odor, microbial spoilage odor and oxidized odor, is one of the most important quality parameter used to determine whether fish is acceptable for consumption or not (Ólafsdóttir, 2005). CO 2 is reported to preserve initial freshness and inhibit the formation of odor associated spoilage, evaluated by different odor attributes that correspond well to bacterial counts (Hansen, Mørkøre, Rudi, Rødbotten et al, 2009;Hansen, Rødbotten, Eie, Lea, Rudi & Mørkøre, 2012). Prediction of sensory quality of cooked fish by measuring odor of raw fillets is also reported (Rødbotten, Lea & Ueland, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, this packaging allows the growth of CO 2 -resistant bacteria, including Gram-positive lactic acid bacteria and the Gram-negative bacterium Photobacterium phosphoreum (2)(3)(4). The latter has been identified as the specific spoilage organism (SSO) responsible for trimethylamine production and sensory spoilage of MAP cod (5,6) and as the main spoilage bacterial species of several chilled marine fish, including cod, garfish, halibut, saithe, salmon, and shrimp (7)(8)(9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%